2015
DOI: 10.1088/0004-637x/804/1/20
|View full text |Cite
|
Sign up to set email alerts
|

PATHWAY TO THE GALACTIC DISTRIBUTION OF PLANETS: COMBINEDSPITZERAND GROUND-BASED MICROLENS PARALLAX MEASUREMENTS OF 21 SINGLE-LENS EVENTS

Abstract: The version presented here may differ from the published version or from the version of the record. Please see the repository URL above for details on accessing the published version and note that access may require a subscription.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
78
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 115 publications
(79 citation statements)
references
References 38 publications
1
78
0
Order By: Relevance
“…A key issue in the analysis of these events has been to break this fourfold degeneracy, in particular the twofold degeneracy that impacts the mass and distance estimates. Although in some cases Zhu et al 2015) this degeneracy has been broken by various fairly weak effects, in the great majority of cases, the degeneracy was broken only statistically (Calchi Novati et al 2015a;Zhu et al 2017b). …”
Section: Microlens Parallax From One and Two Satellitesmentioning
confidence: 99%
See 1 more Smart Citation
“…A key issue in the analysis of these events has been to break this fourfold degeneracy, in particular the twofold degeneracy that impacts the mass and distance estimates. Although in some cases Zhu et al 2015) this degeneracy has been broken by various fairly weak effects, in the great majority of cases, the degeneracy was broken only statistically (Calchi Novati et al 2015a;Zhu et al 2017b). …”
Section: Microlens Parallax From One and Two Satellitesmentioning
confidence: 99%
“…Calchi Novati et al (2015a) showed how the cumulative distribution of planetary events as a function of distance toward the Galactic bulge could be compared to that of the parent sample to determine whether planets are relatively more frequent in the Galactic disk or bulge. However, this comparison depends on the implicit assumption that there is no bias toward the selection of planetary events.…”
Section: Construction Of Blind Tests In the Facementioning
confidence: 99%
“…In addition, Spitzer observations allowed Bozza et al (2016) to break a strong planet/binary degeneracy in the event OGLE-2015-BLG-1212, finding that the companion is a low-mass star and not a planet. These campaigns are the first steps for measuring the Galactic distribution of planets (Calchi Novati et al 2015a), a demographic regime that can currently only be explored by microlensing.…”
Section: Introductionmentioning
confidence: 99%
“…Since 2014, the Spitzer Space Telescope has measured the microlens parallax E p for hundreds of microlensing (single and binary) events, proving it to be an excellent satellite for measuring microlensing parallax (Dong et al 2007;Calchi Novati et al 2015a;Udalski et al 2015b;Yee et al 2015b;Zhu et al 2015). However, the usefulness of Spitzer observations in characterizing binaries can extend beyond measuring parallax.…”
mentioning
confidence: 99%
“…Light curves of single-mass lensing events obtained from ground-based observatories and one space-based observatory typically yield a set of four degenerate solutions (Refsdal 1966;Gould 1994;Gould & Horne 2013;Calchi Novati et al 2015a;Yee et al 2015b), 22 which are often denoted as (+, +), (−, −), (+, −), and (−, +). Here the first and second signs in each parenthesis represent the signs of the lens-source impact parameters as seen from Earth and from the satellite, respectively.…”
mentioning
confidence: 99%